Growth performance, carcass traits and meat quality of growing pigs on different feeding regimes slaughtered at 145 kg BW. Issue 3 (2nd July 2016) - Dalla Bona, Mirco; Schiavon, Stefano; Carraro, Luca; Gallo, Luigi
Abstract: This study investigated the effects of feeding regime on growth performance, carcass traits and meat quality of pigs slaughtered at around 145 kg BW. A total of 96 barrows housed in eight pens were allotted to three groups in each pen. One group was fed ad libitum (AL) and the others were fed according to two quasi AL feeding regimes adjusting feed allowances with increasing BW. At slaughterhouse, the weights of the main lean and fat cuts were recorded, and a sample of longissimus lumborum (LL) was taken for physical and chemical analyses. Average daily gain (ADG) approached 940 g d −1, and gain to feed ratio (G:F) was close to 0.38. Compared with the AL-feeding regime, the feed restriction reduced the pigs' ADG (−3.5%), feed intake (−7.4%) and carcass weight (−3%) ( p < 0.01), but improved their G:F (+ 4%, p < 0.01). Feeding regime did not affect meat quality traits and exerted only minor effects on the weight of primal cuts and on the fatty acid composition of the intramuscular fat of the LL. However, AL-fed pigs tended to yield heavier fat cuts and showed a greater proportion of saturated fatty acid in the LL when compared to restricted feed barrows. In conclusion, moderate restriction in the feeding of medium–heavy pigs seems advisable, as it improves feed efficiency and could cut feed costs compared with the AL-feeding regime without affecting carcass and meat characteristics.